ANALISIS STATUS KEBERLANJUTAN PENGUSAHAAN GARAM DI TIGA WILAYAH PULAU MADURA - Maghfiroh Andriani Astutik; Rita Nurmalina; Burhanuddin Burhanuddin (Jurnal Agribisnis Indonesia, 2019)
This study aims to analyze the sustainability of salt farming based on index assessment using the Rap-Salt method by Multidimensional Scaling (MDS). This research was conducted in three national central salt production in Madura Island, namely Sumenep, Pamekasan and Sampang districts. The data used were primary and secondary data. The primary data was obtained from direct interviews with farmers and some salt experts. The secondary data was obtained from the Statistics Indonesia, the Fisheries and Marine Affairs Office, the Trade Office, and literature that supported this research. The results of the Rap-Salt ordination technique of the MDS method indicate that the sustainability index value in salt farming in three regions on Madura Island ranges from 52,23-53,31. The three regions on Madura Island, respectively, are Pamekasan, Sumenep, and Sampang districts belong to sufficient sustainability category. The analysis of the sustainability of the salt farming in each dimension in five dimensions (ecology, economy, social culture, technology, and institutions) shows that Sumenep Regency has a relatively large index value in several dimensions compared to the other two districts, respectively economy (97,92), culture social (71,70), technology (73,83), and institutional (38,73).